Late Middle Paleolithic of Southern Poland: Radiocarbon dates from Ciemna and Obłazowa Caves. (February 2017) - Alex, Bridget; Valde-Nowak, Paweł; Regev, Lior; Boaretto, Elisabetta
Abstract: New radiocarbon dates are reported for Late Middle Paleolithic (MP) layers of Ciemna and Obłazowa Caves in Southern Poland. The sites present methodological challenges for radiocarbon dating related to post-depositional mixing, materials preservation, and radiocarbon measurements near the detection limit. We describe strategies to address these issues, which allowed for estimation of the timing of lithostratigraphic layers. At Ciemna, bones associated with Late MP artifacts are older than 50 ka. At Obłazowa, bones associated with Late MP artifacts produced dates 50‐45 ka cal BP and a possible Szeletian phase occurred sometime 45‐39 ka cal BP. These new dates add to the regional chronology and strengthen the case that a number of distinct archaeological industries appeared in Southern Poland and Moravia during Marine Isotope Stage 3. Highlights: Radiocarbon dates reported from Late Middle Paleolithic layers at Ciemna and Obłazowa Caves, Poland Methodologies for post-depositional mixing, preservation, and radiocarbon measurement near detection limit Ciemna dates associated with Late MP older than 50 ka Obłazowa dates associated with Late MP between 50-45 ka calBP and possible Szeletian sometime between 45-39 ka calBP